Knowledge, attitudes and practices of healthcare practitioners on falls prevention in Parkinson’s disease patients: a scoping review - Ashari, Asmidawati; Nedunsaliyan, Sankari; Manoharan, Thamayanthi Naidu; Tengku Abdul Hamid, Tengku Aizan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia., 2024)
Parkinson’s disease (PD) is a neurodegenerative disease with progressive in nature, presenting with symptoms such as gait impairments and postural instability that leads to fall with complications such as fractures, disability and mortality. Alarming demands on care by the healthcare practitioners increasing by time. However, there is no study published regarding association between knowledge, attitude and practice (KAP) of healthcare practitioners on fall prevention among PD population. Therefore, this study aims to provide a comprehensive overview of studies dealing with KAP of healthcare practitioners and fall prevention in PD. Methods: The studies published between year 2013 to February 2023 were evaluated.The search was conducted within international electronic databases. A scoping review was conducted using the Arksey and O’Malley framework. All journal articles that focused on the KAP of healthcare practitioners on fall prevention in PD patients were selected. In overall, 5 studies included in this review discussed about studies related to KAP of healthcare practitioners based on screening of result. There were no direct KAP study of healthcare practitioners on falls prevention among PD population. Conclusion: Paucity of literatures observed related to role of healthcare practitioners in falls prevention in PD population.